Oral Melatonin Versus Midazolam as Premedication for Intravenous Sedation in Pediatric Dental Patients - Ghassem Ansari; Mahnaz Fathi; Masoud Fallahinejad Ghajari; Majid Bargrizan; Ahmad Eghbali (Tehran University of Medical Sciences, 2018)
Objectives: This study aimed to evaluate the effect of oral melatonin and oral midazolam as premedication for intravenous (IV) sedation of pediatric dental patients. Materials and Methods: This crossover, double-blind randomized clinical trial was conducted on 23 uncooperative 2-6-year-olds with definitely negative behaviors according to the Frankl's scale. Each child served as their own control. The children were randomly divided into two groups: group I received 0.5mg/kg of oral melatonin one hour before IV sedation, while group II received 0.5mg/kg of oral midazolam 30 minutes before IV sedation on their first visit. Every child received the other premedication on their second visit. The degree of sedation was judged according to the Houpt scale. Physiologic parameters including blood pressure (PB), heart rate (HR), and blood oxygen saturation (SpO2) and side effects including dizziness, nausea, vomiting, and sleepiness were assessed. The parents' and the operator's satisfaction rates were scored. Data were analyzed using paired t-test and Wilcoxon signed-rank test. Results: There were significant differences in sedation scores between the two sessions (P<0.05). However, there were no significant differences in alterations of physiologic parameters between the two sessions (P>0.05). Nausea and vomiting were more common during the first two hours in the midazolam group (P=0.002). Tremors were more common in the melatonin group (P=0.013). Dizziness was more evident when melatonin was used (P<0.001). The clinician and the parents were more satisfied with the results of midazolam intake (P<0.05). Conclusions: Premedication with oral midazolam in pediatric patients is superior to that with melatonin with a higher parents' and operator's satisfaction.